Is there a need to redo many of the diagnoses of hypertension? - Thalenberg, José Marcos; Filho, Bráulio Luna; Bombig, Maria Teresa Nogueira; Francisco, Yoná Afonso; Póvoa, Rui Manuel dos Santos (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Most hypertensive subjects undergoing treatment were diagnosed solely through measurements made in the consultation office. The objective of this study was to redo the diagnosis of treated patients after new clinical measurements and ambulatory blood pressure monitoring (ABPM). DESIGN AND SETTING: Cross-sectional study conducted in an outpatient specialty clinic. METHODS: Patients with mild-to-moderate hypertension or undergoing anti-hypertensive treatment, without target organ damage or diabetes, were included. After drug withdrawal lasting 2-3 weeks, new blood pressure (BP) measurements were made during two separate visits. ABPM was performed blindly, in relation to clinical measurements. The BP thresholds used for diagnosing hypertension, white-coat hypertension, normotension and masked hypertension were: 140 (systolic) and 90 (diastolic) mmHg for office measurements and 135 (systolic) and 85 (diastolic) mmHg for mean awake ABPM (MAA). RESULTS: Evaluations were done on 101 subjects (70% women); mean age 51 ± 10 years. The clinical BP was 155 ± 18/97 ± 10 mmHg (first visit) and 150 ± 16/94 ± 11 mmHg (second visit); MAA was 137 ± 13/ 86 ± 10 mmHg. Sixty-four patients (63%) were confirmed as hypertensive, 28 (28%) as white-coat hypertensive, nine (9%) as normotensive and none as masked hypertensive. After ABPM, 37% of the presumed hypertensive patients did not fit into this category. CONCLUSION: This study showed that hypertension was overdiagnosed among hypertensive subjects undergoing treatment. New diagnostic procedures should be performed after drug withdrawal, with the aid of BP monitoring.